CARDIO-ANKLE VASCULAR INDEX IN PATIENTS WITH CORONARY HEART DISEASE: ASSOCIATION WITH THE SEVERITY OF CORONARY AND PERIPHERAL ARTERY ATHEROSCLEROSIS - A. N. Sumin; A. V. Karpovich; O. L. Barbarash (Российский кардиологический журнал, 2012)
Aim: To investigate the impact of peripheral artery atherosclerosis on the association between cardio-ankle vascular index (CAVI) and coronary atherosclerosis severity in patients with coronary heart disease (CHD). Material and methods. The study included 182 patients (161 men and 21 women; mean age 58,5±7,5 years), examined before the planned intervention on coronary arteries (CA). Based on the values of ankle-brachial index (ABI), all patients were divided into 5 groups: Group I (n=30) with ABI <0,9; Group II (n=28) with ABI 0,9- 0,99; Group III (n=64) with ABI 1,0-1,09; Group IV (n=51) with ABI 1,1-1,3; and Group V (n=9) with ABI >1,3. CAVI was assessed by volume sphygmography method (VaSera VS-1000, Fukuda Denshi, Japan). Coronary angiography was performed with the use of Coroscop and Innova-3100 equipment. Results. In 31,3% of CHD patients, CAVI values exceeded 9,0, which reflected increased arterial stiffness. ABI values below 0,9, as a marker of peripheral artery atherosclerosis, were observed in 16,5%. In Groups I and II, compared to Groups III, IV, and V, mean CAVI values were non-significantly (p=0,1) lower: 7,7±1,95 and 7,9±1,35 vs. 8,3±1,6, 8,2±1,85, and 8,2±2,1, respectively. The percentage of patients with CAVI >9,0 was higher in Group I than in the other groups (10% vs. 29,4- 4,4%; p=0,08). Coronary angiography results were similar in subjects with CAVI values <9,0 vs. >9,0. ABI values were not clearly related to the presence of hemodynamically significant stenosis of two CA, three CA, or left CA trunk. Conclusion. The prevalence of hemodynamically significant CA stenosis was not associated with the vascular indices of interest. The presence of peripheral artery atherosclerosis influenced the link between vascular stiffness (i.e. CAVI) and the severity of CA atherosclerosis. Therefore, the assessment of clinical and prognostic value of CAVI should take into consideration the severity of peripheral atherosclerosis.